Full‐scale simulation of a nearly depleted gas field in South Africa for carbon utilisation and storage. Issue 4 (26th June 2022) - Saffou, Eric; Raza, Arshad; Gholami, Raoof; Aci, Ciriako; Donker, Jan van Bever; Salem, Sofyan; Zimmermann, Udo; Opuwari, Mimonitu; Croukamp, Leon; Elingou, Walter Romaric; Chatterjee, Tapas; Manzi, Musa S.D.
Abstract: Enhanced gas recovery (EGR) is a recognised CO2 utilisation technique that can reduce the cost of carbon storage and improve its economic feasibility. Although there are many studies on the potential of depleted gas fields for CO2 storage, there has not been a comprehensive full‐scale study that can analyse different aspects of carbon utilisation together with the potential of storage, from reservoir characterisation to modelling and economic evaluation. The aim of this study is to develop a benchmark for assessing the technical and economic feasibility of carbon utilisation and storage in abandoned and nearly depleted gas fields. A depleted gas field from the Bredasdorp Basin in South Africa was selected for CO2 ‐EGR and storage, given the availability of data and infrastructure. The reservoir of interest is divided into compartments, with this study focusing exclusively on compartment C1. The gas in place ( Gi ) in compartment C1 was 5.8E+08 MSCF, which was reduced to 3.33E+08 MSCF at the end of the primary production phase. The results obtained indicated that the gas reservoir is very heterogeneous, and a recovery of 20% can be achieved if the injection and production rates are 500 and 3000 MSCF/day, respectively. The amount of CO2 injected after 71 years was about 7.78E+07 MSCF. It was shown that the CO2 in this field can be injected for 71 years without causing problems with the integrity of the reservoir. The economic model was built assuming a project duration of 10 years. The model shows that the total cost of carbon capture, transport and storage is higher than the total revenue for 8 years of natural gas utilisation, which means that the amount of gas recovered from compartment C1 of the reservoir could not offset the cost of CCUS. It is recommended that additional data be collected for the C2 compartment, the carbon capture processes at the Mossel Bay GTL plant, and pipeline transportation to reduce the uncertainty of the proposed economic model. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.